2021
DOI: 10.3390/cryst11010069
|View full text |Cite
|
Sign up to set email alerts
|

Modulation Effect of Hardness on the Friction Coefficient and Its Mechanism Analysis of ZrB2/Mo Multilayers Synthesized by Magnetron Sputtering

Abstract: ZrB2/Mo multilayers were prepared by the magnetron sputtering technique on Si (100) and Al2O3 (001) substrates. The friction behavior and wear mechanism of the multilayers were tested at variable modulation ratios (tZrB2:tMo) of 1:1 to 8:1 at different temperatures. Under the influence of an effective modulation ratio and temperature, the friction coefficient and hardness of ZrB2/Mo multilayers showed an almost opposite change rule, that is, the higher the hardness, the lower the friction coefficient. The hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Alongside the electronic structure, the analysis of spin states is another widely explored research field in the use of ab initio simulations, as shown by Li et al [5] in their study of redox magnetism and electrochromism of a cyclometalated triruthenium complex with triarylamine by means of Monte Carlo and DFT calculations, where they found specific spin and adsorption states that suggest the use of this complex as an electrochromic material for electric field detection. First-principles simulations are also used in combination with experiments to unravel the atomistic origin of specific processes, as in the paper by Zhang et al [6]. The authors performed tribological tests and first-principles calculation of ZrB 2 /Mo multilayers to understand the relation between the hardness of this material and its coefficient of friction, finding that the compound stability is the crucial factor to determine its mechanical properties.…”
mentioning
confidence: 99%
“…Alongside the electronic structure, the analysis of spin states is another widely explored research field in the use of ab initio simulations, as shown by Li et al [5] in their study of redox magnetism and electrochromism of a cyclometalated triruthenium complex with triarylamine by means of Monte Carlo and DFT calculations, where they found specific spin and adsorption states that suggest the use of this complex as an electrochromic material for electric field detection. First-principles simulations are also used in combination with experiments to unravel the atomistic origin of specific processes, as in the paper by Zhang et al [6]. The authors performed tribological tests and first-principles calculation of ZrB 2 /Mo multilayers to understand the relation between the hardness of this material and its coefficient of friction, finding that the compound stability is the crucial factor to determine its mechanical properties.…”
mentioning
confidence: 99%